Aluminum alloy flux-cored welding wire modified by micro-nano particles and preparation method and application thereof

By adding Mo-TiC and yttrium oxide to the aluminum alloy flux-core welding wire, the serious thermal cracking problem of traditional welding wires when welding 7XXX series and 2XXX series aluminum alloys is solved, and the weld strength and thermal stability are significantly improved, and high-quality welding of different aluminum alloys is achieved.

CN116100188BActive Publication Date: 2025-02-28INNER MONGOLIA METAL MATERIAL RES INST
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310184687.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-01
Publication Date
2025-02-28
Estimated Expiration
2043-03-01

AI Technical Summary

Technical Problem

In traditional arc welding technology, solid welding wire is used to weld 7XXX series aluminum alloys or 2XXX series and 7XXX series different aluminum alloys, with severe thermal crack tendency, burning alloy elements, coarse grains, and low weld strength.

Method used

Aluminum alloy flux-core welding wire modified with micro-nanoparticles is used. The welding wire is composed of a pure aluminum tape outer skin and flux-core. The flux-core is filled with alloy elements such as Zn, Mg, Cu, Mn, Cr, and Mo-TiC and yttria stabilized zirconia particles. By adjusting the flux-core formula and micro-nanoparticle composition, the welding quality is improved.

Benefits of technology

It significantly improves the thermal stability and weld strength of the weld, reduces the generation of thermal cracks, and realizes high-quality welding of 2XXX and 7XXX series different aluminum alloys. It is also cheap and easy to obtain, suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a micro-nano particle modified aluminum alloy flux-cored welding wire and a preparation method thereof, wherein the aluminum alloy flux-cored welding wire adopts a pure aluminum strip as an outer skin, and the powder filled in the flux core is prepared by the following components by mass percentage: Zn powder content is 10-30%, Mg powder content is 6.7-19%, Cu powder content is 4.5-11.5%, Mn powder content is 0.5-2.5%, Cr powder content is 0.3-1.5%, Mo-TiC micro-nano particle content is 1-10%, yttria stabilized zirconium oxide particle content is 1-10%, and the balance is pure Al powder. The invention optimizes the traditional flux-cored welding wire by using micro-nano particle materials, effectively solves the problem that 7XXX series high-strength aluminum alloys and 7XXX series and 2XXX series dissimilar aluminum alloys are very easy to generate thermal cracks during welding, thereby significantly improving the thermal stability and weld strength of the weld.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aluminum alloy welding wires, and particularly relates to an aluminum alloy flux-cored welding wire modified by micro-nano particles and a preparation method thereof. Background Art

[0002] Aluminum alloys have been widely used in aerospace, military industry, pressure vessels and other fields due to their low density, good plasticity, high specific strength and low cost, effectively replacing traditional steel.

[0003] Among a series of aluminum alloys, 2XXX and 7XXX aluminum alloys are widely used in aerospace and military fields as a high-strength, heat-treatable aluminum alloy. Although fusion welding is regarded as a more efficient and economical option, existing manufacturing technology still mainly uses mechanical assembly to combine different types of aluminum alloys. In fact, the industry has a great demand for welding involving dissimilar aluminum alloys, because the synergistic effect of welding with different base materials can produce parts with better mechanical properties. However, for 2XXX and 7XXX aluminum alloys, if conventional welding materials are used for welding, a large number of thermal cracks will appear in the weld area, resulting in a significant decrease in weld strength, which seriously limits the application of high-strength aluminum alloys.

[0004] Studies have shown that adding some special micro-nano ceramic particles to welding materials can effectively refine the grains and prevent cracks. TiC micro-nano particles have always attracted much attention as an effective additive to solve aluminum alloy welding cracks. However, the chemical stability of TiC micro-nano particles in molten aluminum is poor, so it is necessary to solidify the Al-TiC system and improve the stability of TiC micro-nano particles in molten aluminum.

[0005] Therefore, there is an urgent need for a special welding wire that can be used for welding dissimilar high-strength aluminum alloys, which can effectively solve the problem of thermal cracks generated by high-strength aluminum alloys during welding and improve the strength of welded joints. More importantly, the new welding wire must be inexpensive, easy to obtain, and have the conditions for large-scale production. Summary of the invention

[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a micro-nano particle modified aluminum alloy flux-cored welding wire, which solves the problems of severe thermal crack tendency, alloy element burnout, coarse grains and low weld strength when solid welding wire is used for welding 7XXX series aluminum alloys or 2XXX series and 7XXX series dissimilar aluminum alloys in traditional arc welding technology.

[0007] The present invention also aims to provide a method for preparing the above-mentioned micro-nano particle modified aluminum alloy flux-cored welding wire.

[0008] In order to solve the above technical problems, the technical solution of the present invention is implemented as follows: a micro-nano particle modified aluminum alloy flux-cored welding wire, the flux-cored welding wire adopts pure aluminum strip as the outer skin, and the powder filled in the flux core is prepared by the following components in mass percentage: Zn powder content is 10-30%, Mg powder content is 6.7-19%, Cu powder content is 4.5-11.5%, Mn powder content is 0.5-2.5%, Cr powder content is 0.3-1.5%, Mo-TiC micro-nano particle content is 1-10%, yttria stabilized zirconia (YSZ) particle content is 1-10%, and the balance is pure Al powder.

[0009] Preferably, the filling rate of the flux core is 20-35%, that is, the mass of the flux powder accounts for 20-35% of the total mass of the flux-cored welding wire.

[0010] Preferably, the Mo-TiC micro-nano particles are Mo-modified TiC micro-nano particles.

[0011] Preferably, the particle size of the Mo-TiC micro-nano particles is 20-30 μm, the purity of the Mo-TiC micro-nano particles is greater than 99.9%, and the shape of the Mo-TiC micro-nano particles is spherical or nearly spherical.

[0012] Preferably, in the Mo-TiC micro-nano particles, the mass percentage of Mo to TiC is controlled between 1:50 and 1:300.

[0013] Preferably, the yttria-stabilized zirconia (YSZ) particles are yttria-doped and modified zirconia particles, the particle size of the yttria-stabilized zirconia (YSZ) particles is 20 to 30 μm, and the shape of the yttria-stabilized zirconia (YSZ) particles is spherical or nearly spherical.

[0014] Preferably, in the yttria-stabilized zirconia (YSZ) particles, the mass percentage of Y2O3 to ZrO2 is controlled between 1:20 and 1:30.

[0015] Preferably, the Zn powder, Mg powder, Cu powder, Mn powder and Cr powder are all high-purity metal powders with a purity greater than 99.9%.

[0016] Preferably, a pure aluminum strip with a width of 8 to 16 mm and a thickness of 0.3 to 1.0 mm is selected as the outer skin of the flux-cored welding wire.

[0017] Another technical solution of the present invention is achieved as follows: a method for preparing the above-mentioned micro-nano particle modified aluminum alloy flux-cored welding wire, characterized in that the method specifically comprises:

[0018] Take pure aluminum strip, remove the oxide film on its surface, and roll it into a U-shaped groove. After adding powder, close the U-shaped groove, and then draw and reduce the diameter through drawing dies of different diameters. After the welding wire is brightened, the finished welding wire is obtained.

[0019] Preferably, the diameter of the welding wire is 1.0-4.0 mm.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1. The present invention optimizes the traditional flux-cored welding wire by using micro-nano particle materials, and can freely adjust the alloy components in the flux-cored formula and the components of the micro-nano particle reinforcement phase according to the components of the base material, effectively solving the problem that 7XXX series high-strength aluminum alloys are very prone to thermal cracking during welding, thereby significantly improving the thermal stability and weld strength of the weld;

[0022] 2. Aiming at the problem of poor chemical stability of TiC micro-nano particles in molten aluminum, the present invention provides a suitable solution, that is, using Mo to modify TiC particles. The addition of Mo will form a Mo-rich coated submicron TiC particle, which can also reduce brittleness by continuous diffusion and segregation into the intermetallic second phase, improve thermal cracking and have higher microhardness and electrical conductivity;

[0023] 3. In view of the scarcity and high price of rare earth metals Sc and Er, the present invention provides a suitable substitute, that is, yttria-stabilized zirconia (YSZ) is used to replace traditional Sc and Er equivalently, and by increasing the Al3Zr nucleation sites, inducing grain refinement to avoid the formation of coarse columnar grains, forming ultrafine submicron-sized equiaxed grain bands, fundamentally inhibiting the occurrence of thermal cracks.

[0024] 4. In addition to welding the same type of 7XXX series aluminum alloy parent material, by adjusting the content of various alloy components and micro-nano particle components in the flux core, the flux-cored welding wire of the present invention can be used to weld dissimilar aluminum alloys of 7XXX series and 2XXX series aluminum alloys, and a higher quality weld joint can be obtained.

[0025] 5. The welding wire prepared by the present invention is low-priced, easy to obtain, and has the conditions for industrial production. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0027] It should be noted that the raw materials used in the following specific embodiments can be obtained by purchase or self-production.

[0028] The embodiment of the present invention provides a micro-nano particle modified aluminum alloy flux-cored welding wire, which adopts a pure aluminum strip as an outer skin, and the powder filled in the flux core is prepared by the following components in mass percentage: Zn powder content is 10-30%, Mg powder content is 6.7-19%, Cu powder content is 4.5-11.5%, Mn powder content is 0.5-2.5%, Cr powder content is 0.3-1.5%, Mo-TiC micro-nano particle content is 1-10%, yttria stabilized zirconia particle content is 1-10%, and the balance is pure Al powder.

[0029] Furthermore, the filling rate of the flux core is 20-35%, that is, the mass of the flux powder accounts for 20-35% of the total mass of the flux cored welding wire; the Mo-TiC micro-nano particles are Mo-modified TiC micro-nano particles; the particle size of the Mo-TiC micro-nano particles is 20-30 μm, the purity of the Mo-TiC micro-nano particles is greater than 99.9%, and the shape of the Mo-TiC micro-nano particles is spherical or nearly spherical; in the Mo-TiC micro-nano particles, the mass percentage of Mo to TiC is controlled between 1:50 and 1:300; the yttria-stabilized zirconia (Y The YSZ particles are yttria-doped modified zirconium oxide particles, the particle size of the yttria-stabilized zirconia (YSZ) particles is 20-30 μm, and the shape of the yttria-stabilized zirconia (YSZ) particles is spherical or nearly spherical; in the yttria-stabilized zirconia particles, the mass percentage of Y2O3 to ZrO2 is controlled between 1:20 and 1:30; the Zn powder, Mg powder, Cu powder, Mn powder and Cr powder are all high-purity metal powders with a purity greater than 99.9%; a pure aluminum strip with a width of 8-16 mm and a thickness of 0.3-1.0 mm is selected as the outer skin of the flux-cored welding wire.

[0030] The embodiment of the present invention also provides a method for preparing the above-mentioned micro-nano particle modified aluminum alloy flux-cored welding wire, which specifically comprises:

[0031] Take a pure aluminum strip, remove the oxide film on its surface, and roll it into a U-shaped groove. After adding powder, close the U-shaped groove, and then draw and reduce the diameter through drawing dies of different diameters. Then, the welding wire is brightened to obtain a finished welding wire; the diameter of the welding wire is 1.0-4.0 mm.

[0032] The present invention organically combines flux-cored welding wire technology and micro-nano particle modification technology to solve the problems of serious hot crack tendency, alloy element burnout, coarse grains, low weld strength, etc. when solid welding wire in traditional arc welding technology is used to weld 7XXX series aluminum alloy. More importantly, the micro-nano particle modified aluminum alloy flux-cored welding wire prepared by the present invention can adjust the alloy composition and the composition of the micro-nano particle reinforcement phase in the flux core formula according to the parent material composition, thereby realizing the welding of 2XXX series and 7XXX series dissimilar aluminum alloys, and significantly reducing hot cracks, and obtaining a weld joint with beautiful shape and excellent mechanical properties.

[0033] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with specific embodiments.

[0034] Example 1

[0035] A micro-nano particle modified aluminum alloy flux-cored welding wire for welding 7075 ultra-high strength aluminum alloy, using 1070 pure aluminum strip outer skin 10×1mm, filling rate 24%, the filling wire after drawing and reducing the diameter of 1.2mm. The chemical composition of the flux core is 26% metal Zn powder content, 12% metal Mg powder content, 7.5% metal Cu powder content, 0.9% metal Mn powder content, 1.0% metal Cr powder content, 8% composite micro-nano Mo-TiC particle content, and the balance is pure aluminum powder.

[0036] Example 2

[0037] A micro-nano particle modified aluminum alloy flux-cored welding wire for welding 7075 ultra-high strength aluminum alloy, using 1070 pure aluminum strip outer skin 12×0.8mm, filling rate 28%, the filling wire after drawing and reducing the diameter of 1.6mm. The chemical composition of the flux core is 22% metal Zn powder content, 10% metal Mg powder content, 6.5% metal Cu powder content, 0.7% metal Mn powder content, 0.75% metal Cr powder content, 6.5% composite micro-nano Mo-TiC particle content, and the balance is pure aluminum powder.

[0038] Example 3

[0039] A micro-nano particle modified aluminum alloy flux-cored welding wire for welding 7075 ultra-high strength aluminum alloy, using 1070 pure aluminum strip outer skin 10×1mm, filling rate 25%, the filling wire after drawing and reducing the diameter of 1.2mm. The chemical composition of the flux core is 24% metal Zn powder content, 11% metal Mg powder content, 7.2% metal Cu powder content, 0.8% metal Mn powder content, 0.85% metal Cr powder content, 4% composite micro-nano Mo-TiC particles content, 4% composite micro-nano YSZ particles content, and the balance is pure aluminum powder.

[0040] Example 4

[0041] A micro-nano particle modified aluminum alloy flux-cored welding wire for welding 7075 ultra-high strength aluminum alloy, using 1070 pure aluminum strip outer skin 12×0.8mm, filling rate 30%, the filling wire after drawing and reducing the diameter of 1.6mm. The chemical composition of the flux core is 20% metal Zn powder content, 9% metal Mg powder content, 6% metal Cu powder content, 0.7% metal Mn powder content, 0.7% metal Cr powder content, 4% composite micro-nano Mo-TiC particles content, 4% composite micro-nano YSZ particles content, and the balance is pure aluminum powder.

[0042] Example 5

[0043] A micro-nano particle modified aluminum alloy flux-cored welding wire for welding 7075 and 2024 dissimilar high-strength aluminum alloys, using a 1070 pure aluminum strip outer skin of 10×1mm, a filling rate of 30%, and a filling wire with a diameter of 1.2mm after drawing and reducing. The chemical composition of the flux core is 12% metal Zn powder content, 16% metal Mg powder content, 9.5% metal Cu powder content, 1.5% metal Mn powder content, 0.5% metal Cr powder content, 4% composite micro-nano Mo-TiC particle content, 4% composite micro-nano YSZ particle content, and the balance is pure aluminum powder.

[0044] Comparative Example 1

[0045] The invention discloses an aluminum alloy welding wire used for welding 7075 ultra-high strength aluminum alloy. The filler wire is an ER7075 solid core welding wire with a diameter of 1.2 mm.

[0046] Comparative Example 2

[0047] An aluminum alloy flux-cored welding wire for welding 7075 ultra-high strength aluminum alloy, using 1070 pure aluminum strip outer skin 12 × 0.8mm, filling rate 30%, the filling wire after drawing and reducing the diameter of 1.2mm. The chemical composition of the flux core is 20% metal Zn powder content, 9% metal Mg powder content, 6% metal Cu powder content, 0.7% metal Mn powder content, 0.7% metal Cr powder content, the balance is pure aluminum powder.

[0048] Comparative Example 3

[0049] A micro-nano particle modified aluminum alloy flux-cored welding wire for welding 7075 and 2024 dissimilar high-strength aluminum alloys, using 1070 pure aluminum strip outer skin 10×1mm, filling rate 30%, the filling wire after drawing and reducing the diameter of 1.2mm. The chemical composition of the flux core is 12% metal Zn powder content, 16% metal Mg powder content, 9.5% metal Cu powder content, 1.5% metal Mn powder content, 0.5% metal Cr powder content, and the balance is pure aluminum powder.

[0050] Table 1 Comparison of flux core ratios and weld performance in various embodiments and comparative examples

[0051]

[0052] The chemical composition (wt%) (balance is Al) of the 1070 pure aluminum strip, 2024 and 7075 aluminum alloy test plates used in Examples 1-5 and Comparative Examples 1-3 was tested, and the test results are as follows:

[0053] Table 2 Chemical composition (wt%) of 1070 pure aluminum strip, 2024 and 7075 aluminum alloy test plates used in the embodiments and comparative examples (the balance is Al)

[0054]

[0055] The aluminum alloy flux-cored welding wires prepared in Examples 1-5 and Comparative Examples 1-3 were subjected to welding tests: the test plates were 10 mm thick 7075 and 2024 aluminum alloy test plates, the welding current was 170-200 A, the welding speed was 300-350 mm / min, and the gas flow rate was 15-20 L / min. Welding was performed in the flat welding position, and the mechanical properties, porosity sensitivity, crack resistance and other properties of the test plates were evaluated after welding.

[0056] The mechanical properties of welded joints were evaluated according to the standards GB / T2651-2008 "Welded Joint Tensile Test Method" and GB / T228.1-2010 "Metallic Material Tensile Test Part 1: Room Temperature Test Method". The porosity sensitivity was evaluated by photographing the weld of the test plate with X-rays, and the quality grade of the welded joint was evaluated according to the standard NB / T 47013.2-2015 "Pressure Equipment Nondestructive Testing Part 2: Radiographic Testing". The crack resistance was evaluated by ultrasonic diffraction on the welded test plate. No macroscopic and microscopic cracks were found, which was recorded as good, a certain amount of microscopic cracks were recorded as fair, and a large number of microscopic cracks or macroscopic cracks were recorded as unqualified.

[0057] The results show that the welding wire within the formula range of the present invention has good processability during welding, beautiful weld formation, excellent mechanical properties and crack resistance; however, the welding wire outside the patent formula range or not using the welding method of the present invention has poor overall processability, mechanical properties and crack resistance.

[0058] The above is only a preferred specific implementation of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A micro-nano particle modified aluminum alloy flux-cored welding wire, characterized in that: The flux-cored welding wire adopts a pure aluminum strip as an outer skin, and the powder filled in the flux core is prepared by the following components according to mass percentage: Zn powder content is 10-30%, Mg powder content is 6.7-19%, Cu powder content is 4.5-11.5%, Mn powder content is 0.5-2.5%, Cr powder content is 0.3-1.5%, Mo-TiC micro-nano particle content is 1-10%, yttria stabilized zirconium oxide particle content is 1-10%, and the balance is pure Al powder; the filling rate of the flux core is 20-35%, that is, the mass of the powder accounts for 20-35% of the total mass of the flux-cored welding wire; in the Mo-TiC micro-nano particles, the mass percentage of Mo and TiC is controlled between 1:50 and 1:

300.

2. The micro-nano particle modified aluminum alloy flux-cored welding wire according to claim 1, characterized in that: The Mo-TiC micro-nano particles are TiC micro-nano particles modified with Mo.

3. The micro-nano particle modified aluminum alloy flux-cored welding wire according to claim 1, characterized in that: The particle size of the Mo-TiC micro-nano particles is 20-30 μm, the purity of the Mo-TiC micro-nano particles is greater than 99.9%, and the shape of the Mo-TiC micro-nano particles is spherical or nearly spherical.

4. The micro-nano particle modified aluminum alloy flux-cored welding wire according to claim 1, characterized in that: The yttria-stabilized zirconia particles are zirconia particles modified by yttria-doped particles. The particle size of the yttria-stabilized zirconia particles is 20-30 μm, and the shape of the yttria-stabilized zirconia particles is spherical or nearly spherical.

5. The micro-nano particle modified aluminum alloy flux-cored welding wire according to claim 1, characterized in that: In the yttria-stabilized zirconia particles, the mass percentage of Y2O3 to ZrO2 is controlled between 1:20 and 1:

30.

6. The micro-nano particle modified aluminum alloy flux-cored welding wire according to claim 1, characterized in that: The Zn powder, Mg powder, Cu powder, Mn powder and Cr powder are all high-purity metal powders with a purity greater than 99.9%.

7. The micro-nano particle modified aluminum alloy flux-cored welding wire according to claim 1, characterized in that: A pure aluminum strip with a width of 8 to 16 mm and a thickness of 0.3 to 1.0 mm is selected as the outer skin of the flux-cored welding wire.

8. A method for preparing the micro-nano particle modified aluminum alloy flux-cored welding wire according to any one of claims 1 to 7, characterized in that: The method is as follows: Take a pure aluminum strip, remove the oxide film on its surface, and roll it into a U-shaped groove. After adding powder, close the U-shaped groove, and then draw and reduce the diameter through drawing dies of different diameters. Then, the welding wire is brightened to obtain a finished welding wire; the diameter of the welding wire is 1.0-4.0 mm.

Citation Information

Patent Citations

  • High wear resistance surfacing alloy material containing multiphase metal ceramics

    CN101879670A

  • Micro-nano particle reinforced aluminum alloy flux-cored filler wire used for TIG welding of 7075 aluminum alloy

    CN111015012A

  • Flux-cored aluminum brazing filler metal and preparation method thereof

    CN112621015A

  • Solid-state phase change composite brazing filler metal based on yttria-stabilized zirconia and preparation method of solid-state phase change composite brazing filler metal

    CN114147388A